DEVELOPMENT OF CLUSTER-BASED VR-APPLICATIONS USING OPENSCENEGRAPH - Wardijono, Bheta Agus; LÃ¶wen, Johann (Jurnal Ilmiah Informatika Komputer, 2009)
In this paper we will describe about a development the cluster-based VR-Applications using OpenSceneGraph. The OpenSceneGraph does not support cluster, so it is not possible to use the OpenSceneGraph without modifications for development of cluster-based VR-Applications. In this paper we will show how the OpenSceneGraph could be extended to be used for the development of cluster-based VR-ApplicationKeyword(s): OpenSceneGraph, CAVE, Cluster, VR-Applications, computer graphicsSubject description: I.3. Computer Graphic | I.3.7.Three-Dimensional Graphics and Realism | Virtual Reality